Analyzing influencing factors to scale up agroforestry systems in Colombia: A comparative ex-ante assessment of cacao farming and cattle ranching in two regions - Rodríguez, Tatiana; Bonatti, Michelle; Lohr, Katharina; Lana, Marcos A.; Rio Duque, Martha Lilia del; Stefan Sieber (Springer, 2022)
Agroforestry systems (AFS) are proved to enhance sustainable land management. Thus, there is increasing demand for effective ways to scale up AFS so that more people can benefit. Consequently, this study assesses the scaling-up potential of agroforestry systems (AFS) using cacao farming and cattle ranching in Caquetá and Cesar, Colombia, as examples. An ex-ante assessment using the ScalA tool is conducted through interviews with AFS experts from institutions promoting AFS. Using a comparative approach, results reveal that AFS have different scaling-up potential depending on the type of farming system and location characteristics. In our case, it is slightly higher for cacao farming than for cattle ranching in both regions and it is higher in Caquetá than in Cesar for both systems. Factors hindering the scaling-up potential for both regions are economic conditions at the local and regional levels since there is a lack of stable and differentiated markets to absorb AFS products. In contrast, the scaling-up potential in both regions is increased by the factors related to the capacity of the organizations that promote AFS and the attitudes of local communities toward them. The study generates information about factors that may hinder or foster AFS scaling-up, including not just the capacities and mechanisms to promote them but also the enabling conditions. This contributes to prioritizing AFS interventions and better allocating their resources to increase their chances of successful scaling-up.